2005
DOI: 10.1111/j.1365-2125.2004.02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Melphalan pharmacokinetics in children with malignant disease: influence of body weight, renal function, carboplatin therapy and total body irradiation

Abstract: AimTo analyse the pharmacokinetics of melphalan in 52 children (0.3-18 years) and determine whether any clinical factors affect the pharmacokinetic parameters Additionally, to examine whether a test melphalan dose can predict the pharmacokinetics of a full dose, when there are 5 intervening days of carboplatin therapy. MethodsMelphalan concentrations were measured in 14 blood samples collected from each child following doses ranging from 30 to 180 mg m -2 . The pharmacokinetics were analysed with Kinetica 4.0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 28 publications
8
30
0
Order By: Relevance
“…Our pharmacokinetic results (Table V) of melphalan given with concurrent BSO are similar to those reported in children for melphalan alone or given with other agents excluding carboplatin, which is known to decrease melphalan clearance and volume of distribution. [38,39] This suggests that BSO does not affect melphalan PK. Other studies of high-dose melphalan (140-180 mg/m 2 ) showed similar systemic clearance results ranging from 15.4 to 29.9 l/hr/m 2 .…”
Section: Discussionmentioning
confidence: 95%
“…Our pharmacokinetic results (Table V) of melphalan given with concurrent BSO are similar to those reported in children for melphalan alone or given with other agents excluding carboplatin, which is known to decrease melphalan clearance and volume of distribution. [38,39] This suggests that BSO does not affect melphalan PK. Other studies of high-dose melphalan (140-180 mg/m 2 ) showed similar systemic clearance results ranging from 15.4 to 29.9 l/hr/m 2 .…”
Section: Discussionmentioning
confidence: 95%
“…In children, melphalan is currently dosed on a mg m −2 basis, and there are no guidelines for varying the dose in patients who are very heavy or who have impaired renal function. Many studies have noted wide variability in exposure in patients receiving the same surface area‐based dose [9, 10]. Children with high melphalan exposure have been previously shown to have increased toxicity [11], demonstrating a relationship between melphalan pharmacokinetics and melphalan toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…There are two studies that have reported no pharmacokinetic interaction between carboplatin and etoposide , and one study has reported an interaction between melphalan and carboplatin . As these drugs were coadministered in all patients in the present study, potential drug–drug interactions could not be investigated directly.…”
Section: Discussionmentioning
confidence: 81%